BIOLOGICAL RELATIONSHIP BETWEEN INSULIN-LIKE GROWTH FACTORS (IGF1 AND IGF2) GENES AND STEROIDOGENESIS IN OVINE OVARIAN ANTRAL FOLLICLES - AHMED, SHILAN J.; MOHAMMED, BUSHRA T. (Journal of Duhok University, 2022)
Reproductive inefficiency in sheep is a critical source of reduction in small ruminant profitability worldwide. The importance of insulin-like growth factors1 and 2 belonging to the insulin-like growth factors system were identified as pivotal key roles in ovarian follicular development and steroidogenesis in different species. This study aimed to detect the IGF-1 and IGF-2 genes and Oestrogen levels in the ovine small and large antral follicles collected from an abattoir using conventional PCR and ELISA, respectively, as well as to investigate the relationships between IGFs genes and steroidogenesis using bioinformatics approaches. Our results showed that IGF-1, IGF-2, and CYP19A1 were significantly present in the local sheep ovary’s small and large antral follicles. Furthermore, the oestrogen levels were significantly different between these two ovarian follicle types. The string database suggested that IGFs and CYP19 have strong relationships. Functional annotation (GO terms) revealed that IGFs and CYP19 genes were mainly associated with responses to hormone and insulin growth factor bindings. In addition, KEGG pathways mapped to ovarian steroidogenesis and Ras signaling pathways. Overall, these findings are consistent with the critical functions of IGF-1 and IGF-2 in regulating steroidogenesis, growth, and viability of follicular cells in the sheep ovary. Therefore, evaluation of IGFs genes can be useful for the understanding of reproduction performance in ewes